OVERVIEW OF PUBLIC KNOWLEDGE ABOUT STROKE IN THE WORK AREA OF KAWAL PUBLIC HEALTH CENTER - Romalina Romalina; Asmarita Jasda; Meisa Daniati; Artia Diarina; Yas Suriani (Bajang Institute, 2021)
Stroke is a disorder of the central nervous system that is most often found and is the main cause of impaired functional activity in adults. The prevalence of stroke incidence based on RISKESDAS tajun 2018 is increasing from 7% to 10.9% at the age of ≥ 15 years. Stroke attacks can cause weakness and paralysis in one or even both sides of the patient's body, this weakness can cause difficulties when walking and doing activities. The degree of disability experienced by stroke patients depends on the severity of hemiparesis, 30-60% of patients who experience hemiparesis will experience a complete loss of body functions within 6 months after the stroke. The purpose of this study is to provide an overview of public knowledge about stroke in the work area of the Kawal public Health Center.. The method in the study was a descriptive survey of the knowledge of the community in the working area of the Kawal Public Health Center, Riau Islands Province, about stroke. The study was carried out in July 2020 with a total sample of 39 respondents. The results of the study were obtained where the picture of public knowledge about stroke with good knowledge was 16 people (41.02%) and sufficient knowledge as many as 7 people (17.94%). Suggestions need to improve health promotion about stroke through print or electronic media and further research on the identification of stroke risk factors in the community of the Kawal Public Health Center work area.